Effect of Topical Intra-Auricular Lidocaine on Tinnitus: A Randomized Double-Blind Placebo-Controlled Study - Campos, Tatiane Vacaro; Bento, Ricardo Ferreira; Oticica, Jeanne; Jabour, Maíra Said; Távora, Nathália; Jardim, Isabela; de Marchi, Cristiane Leite; Tsuji, Robinson Koji (International Archives of Otorhinolaryngology, 2025)
Tinnitus is a prevalent symptom and has no proven effective treatment. Clinical observations that some patients reported significantly improved tinnitus after topical ear drop administration of lidocaine motivated research on this drug.Evaluate the action of topical intra-auricular 10% lidocaine in suppressing tinnitus compared to placebo.This was a randomized, crossover, double-blind, placebo-controlled clinical trial. The variations of the visual analog scale (VAS), tinnitus loudness, and the minimum masking level (MML) after intra-auricular lidocaine 10% were compared with a placebo. The same variables were compared with some sample features.There was no statistically significant difference between the action of lidocaine and placebo in tinnitus variation measured by VAS (p = 0.361), tinnitus loudness (p = 0.850), and MML. (p = 0.213). The VAS variation was statistically lower in patients with any hearing loss (p = 0.005); the tinnitus loudness variation was higher in patients with tinnitus modulation (p = 0.049) and lower in patients with any hearing loss (p = 0.045). The MML variation was lower in patients with bruxism/TMD (p = 0.026).In this study the action of lidocaine on the variation of tinnitus intensity was similar to placebo. We believe that the use of manipulated medication may have interfered in the outcome and that the large number of patients with positive response to placebo should be investigated in further studies.
Keywords: tinnitus; lidocaine; external acoustic meatus; local anesthetics; topical administration; clinical trial